Application of the Huff’s probability model on selected large-area retail units in Košice in the context of transformational changes in retail after 1989 in Slovakia - Fertaľová, Jana; Varga, Pavol (Revija za geografijo, 2007)
After 1989 there have been rather significant qualitative and spatial changes in retail trade network in Slovakia. The behaviour of trader as well as consumer is changing. Supranational trade networks with their large hypermarkets are penetrating our trade. In last four years the share of hypermarket shopping in Slovakia has increased more than twice, and the share of small shops and counter shops is decreasing despite the fact that they keep the highest average annual shopping frequention. Hypermarkets continuously make a profit of new customers.